Private equity investment, exit strategy and IPO performance: evidence from Indian IPOs. (2018) - ,; Katti, Supriya; Phani, B.V.
Private equity (PE) is one of the important sources of financing. The certification hypothesis associated with PE investment influences the performance during the process of going public. The listing day performance of initial public offerings (IPO) is significantly influenced by various financial intermediaries involved in the IPO process due to certification effect associated with their reputation. In this study we try to evaluate certification and grandstanding hypothesis associated with PE investors in IPO market. Our empirical results refute certification hypothesis since the PE investment does influence the IPO performance. However, the ownership stake of PE investment has negative impact on the first day of IPO performance. This supports grandstanding hypothesis where the ownership stake and the urge of PE investors in liquidating the stake determines the IPO performance. The insignificant ownership stake held by private equity investors is a consequence of regulatory constraint. The insignificant impact on long-term IPO performance is also due to insignificant ownership stake retained after IPO. In addition, it is also observed that business group affiliated firms have lower degree of IPO underpricing. The overall performance of IPO follows 'U' shape curve indicating positive performance in the short term and long-term.